2018
DOI: 10.29252/jabr.01.01.07
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between EBV Virus and Breast Cancer in Khuzestan Province of Iran

Abstract: Breast cancer is the most frequently diagnosed cancer among women worldwide. 1 The incidence of breast cancer in Iran is about 20 new cases per 100 000 women-years. 2 This cancer often leads to complete removal of breast tissue, chemotherapy, radiotherapy and hormonotherapy. 3 Several internal and external factors contribute to the development of this cancer. Internal factors such as age, hormonal effects, lifestyle, obesity, alcohol consumption, smoking, gender, anxiety and stress, genetic predisposition (mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…53 In contrast, a low percentage of EBV DNA was also found in 5.12% of FFPE tissues of Iranian women. 54 However, EBV DNA was not detected in FFPE tissues of Iranian women using PCR targeting the Bam HI-H rightward open reading frame 1 (BHRF1) region. 55 Moreover, EBV DNA was detected using PCR in 20% of fresh tissues of Egyptian BC patients, 56 4.7% of Mexican BC patients, 57 and 31% of Argentinian BC patients.…”
Section: Discussionmentioning
confidence: 99%
“…53 In contrast, a low percentage of EBV DNA was also found in 5.12% of FFPE tissues of Iranian women. 54 However, EBV DNA was not detected in FFPE tissues of Iranian women using PCR targeting the Bam HI-H rightward open reading frame 1 (BHRF1) region. 55 Moreover, EBV DNA was detected using PCR in 20% of fresh tissues of Egyptian BC patients, 56 4.7% of Mexican BC patients, 57 and 31% of Argentinian BC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 6.8% (7/102) of samples comprised 11.76% (6/51) in malignant tissues and 1.9% (1/51) in adjacent non-malignant tissues found to be positive for presence of EBV genome, which was statistically significant (P<0.05).Similar to our results, several case-control reports from Iran and other parts of the world have demonstrated higher prevalence of EBV in malignant tumors as compared with control groups. In several studies, the prevalence rate of EBV in malignant breast tissues and nonmalignant control groups were as follows: 9.3% and 0% in a study by Aghdam et al (Iran, 2017), 8% and 0% in a study by Malekpour et al (Iran, 2015), 5.1% and 0% in a study by Saeedi et al (Iran, 2018), 10% and 0% in a study by Antonsson et al (Australia, 2012), 13.6% and 4.5% in a study by Ladera et al (Venezuela, 2017), respectively (28)(29)(30)(31)(32). It is noteworthy that despite other investigations, our study used adjacent non-malignant tissues to improve the accuracy of viral causality in the development of malignancy.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, they reported that EBV was found in 5.12% of breast cancer tissue but reported that there were no significant relationships between breast cancer and EBV. [ 30 ] These differences could be justified based on the regional differences. In 2021, a study was performed by Sinclair et al .…”
Section: Discussionmentioning
confidence: 99%